Education, Income and Parenting Patterns in relation to Toddler Temper Tantrum Incidents and Parents Using Smartphones - Wiliyanarti, Pipit Festi; Riswanti, Priska Indah; Reliani, Reliani; Rofiqi, Erfan; Rozifa, Annisa’ Wigati (Gaceta Médica de Caracas, 2022)
Developmental disorders for toddlers are still a health problem today. Temper tantrums are an expression of extreme frustration that is described through the behavior of crying, shouting, and slamming things. Many factors can influence this condition, one of which is the background that the parents have. The purpose of this study was to determine the relationship between education, income, parenting patterns, and the incidence of toddler temper tantrums for parents who are active smartphone users.